2003
DOI: 10.1097/01.asn.0000043904.26730.11
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Natriuresis in AT2 Receptor–Deficient Mice with L-NAME Hypertension

Abstract: Abstract. AT 2 receptor-disrupted (AT 2 Ϫ/Ϫ) mice provide a unique opportunity to investigate the cardiovascular and BP-related effects of NO depletion. This study compared the pressure-diuresis-natriuresis relationship in (AT 2 Ϫ/Ϫ) and wild-type (AT 2 ϩ/ϩ) mice after treating the animals with L-NAME (130 mg/kg body wt per day) for 1 wk. L-NAME increased mean arterial pressure (MAP) more in AT 2 Ϫ/Ϫ than in AT 2 ϩ/ϩ mice (118 Ϯ 2 versus 108 Ϯ 4 mmHg). This difference occurred even though L-NAME-treated AT 2 ϩ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…Consistent with our present findings, Chatziantoniou et al (7) found that in mice, chronic L-NAME treatment produced a gradual increase in arterial pressure (measured by tail cuff) over a period of 14 wk. Other studies have also demonstrated pressor responses to L-NAME, administered via the drinking water, of comparable magnitude to that which we observed in the present study (2,29,30,32). The fact that MAP was lower in mice treated chronically with L-NAME than in eNOS Ϫ/Ϫ mice may reflect incomplete blockade of NOS by this oral L-NAME treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our present findings, Chatziantoniou et al (7) found that in mice, chronic L-NAME treatment produced a gradual increase in arterial pressure (measured by tail cuff) over a period of 14 wk. Other studies have also demonstrated pressor responses to L-NAME, administered via the drinking water, of comparable magnitude to that which we observed in the present study (2,29,30,32). The fact that MAP was lower in mice treated chronically with L-NAME than in eNOS Ϫ/Ϫ mice may reflect incomplete blockade of NOS by this oral L-NAME treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Baseline values of GFR in KO mice were not significantly different from those in WT mice as reported previously (13). The inhibition of NOS was also reported to have none or minimal effect on GFR in many studies (6,19,23,24,29,36). These findings are consistent with the concept that NO exerts a proportionate influence on both preglomerular and postglomerular resistance segments (28).…”
Section: Discussionsupporting
confidence: 71%
“…It may be that overexpression of AT 2 -R protects against the hypertensive effect of L-NAME as a previous study demonstrated that AT 2 -R null mice demonstrated significantly greater blood pressure response to L-NAME than WT controls. 26 …”
Section: Discussionmentioning
confidence: 99%